2019
DOI: 10.1002/qute.201800058
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Nanowires for Single‐Photon Detection: Progress, Challenges, and Opportunities

Abstract: Single-photon detectors and nanoscale superconducting devices are two major candidates for realizing quantum technologies. Superconducting-nanowire single-photon detectors (SNSPDs) comprise these two solid-state and optic aspects enabling high-rate (1.3 Gb s −1 ) quantum key distribution over long distances (>400 km), long-range quantum communication (>1200 km), as well as space communication (239 000 miles). The attractiveness of SNSPDs stems from competitive performance in the four single-photon relevant cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(75 citation statements)
references
References 249 publications
(679 reference statements)
2
68
0
Order By: Relevance
“…The most successful candidates are Nb(Ti)N, WSi, and MoSi, which have an SDE of more than 90%. A general discussion on the materials will be given here instead of a detailed performance comparison, which can be found elsewhere [29].…”
Section: Candidate Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most successful candidates are Nb(Ti)N, WSi, and MoSi, which have an SDE of more than 90%. A general discussion on the materials will be given here instead of a detailed performance comparison, which can be found elsewhere [29].…”
Section: Candidate Materialsmentioning
confidence: 99%
“…Encouraged by the major success of the SNSPDs in QI, this review focuses on the SNSPDs and their applications in QI, although other impressive applications, such as deep-space communication [26] and light detection and ranging [27,28], are available. Furthermore, some general or specific reviews of SNSPDs can be found [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed overview of the detection mechanisms and SNSPDs in general can be found in refs. []. Typical superconductors are niobium nitride (NbN), niobium titanium nitride (NbTiN), tungsten silicide (WSi), tantalum nitride (TaN), molybdenum silicide (MoSi) making the realization of SNSPDs on a variety of quantum photonic material platforms as GaAs, Si, SiN, AlN, and LiNbO 3 possible .…”
Section: Gaas‐based Photonic Integrated Circuitsmentioning
confidence: 99%
“…[]. Typical superconductors are niobium nitride (NbN), niobium titanium nitride (NbTiN), tungsten silicide (WSi), tantalum nitride (TaN), molybdenum silicide (MoSi) making the realization of SNSPDs on a variety of quantum photonic material platforms as GaAs, Si, SiN, AlN, and LiNbO 3 possible . The advantage of the nitride‐based superconductors is the high critical temperature which is, for example, in the range of 7–11.5 K for thin NbN films (2–5 nm) making the operation at liquid helium temperatures at 4 K possible .…”
Section: Gaas‐based Photonic Integrated Circuitsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] As compared to their bulk counterparts, the use of NWs in photoconductors is of particular interest to quantum communications, sensing and imaging applications owing to their higher sensitivity and faster response speed. [8][9][10][11] To maximize the detection efficiency, semiconductor NWs are usually removed from growth substrate and placed horizontally on a secondary substrate to ease contact fabrication and also to increase their photosensitive area. However, the nanoscale active area of the NWs leads to small absorption cross-section and hence low external quantum efficiency (EQE) and poor responsivity.…”
Section: Introductionmentioning
confidence: 99%